2008
DOI: 10.1002/hep.22027
|View full text |Cite
|
Sign up to set email alerts
|

Association of gankyrin protein expression with early clinical stages and insulin-like growth factor-binding protein 5 expression in human hepatocellular carcinoma

Abstract: Gankyrin (also known as PSMD10) is a liver oncoprotein that interacts with multiple proteins including MDM2 and accelerates degradation of the tumor suppressors p53 and Rb. We produced a monoclonal anti-gankyrin antibody and immunohistochemically assessed the clinicopathological significance of gankyrin overexpression in 43 specimens of human hepatocellular carcinoma (HCC). Specific cytoplasmic staining for gankyrin was observed in 62.8% (27/43) of HCCs, which was significantly associated with low TNM stage (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Most authors have reported that the prevalent type of HCC is of a moderately differentiated to well-differentiated grade with β-catenin expression at the membrane and in the cytoplasm [14,29,30]. These conclusions are consistent with recent results showing that p28 GANK plays an oncogenic role primarily at the early stages of human hepatocarcinogenesis [36]. β-catenin can enter the nucleus and regulate the transcription of target genes such as cyclin D1 and c-Myc [10,30].…”
Section: Discussionsupporting
confidence: 81%
“…Most authors have reported that the prevalent type of HCC is of a moderately differentiated to well-differentiated grade with β-catenin expression at the membrane and in the cytoplasm [14,29,30]. These conclusions are consistent with recent results showing that p28 GANK plays an oncogenic role primarily at the early stages of human hepatocarcinogenesis [36]. β-catenin can enter the nucleus and regulate the transcription of target genes such as cyclin D1 and c-Myc [10,30].…”
Section: Discussionsupporting
confidence: 81%
“…22 When gankyrin was silenced in hepatocellular carcinoma cell lines with wt and mutated P53, a different phenotype was induced in the wt P53 cells, with up-regulation of p53 levels and subsequent activation of caspase 9 and induction of apoptosis. 33 Our results showed stronger inhibition of cell growth and a greater pro-apoptotic effect after miR-214 transfection in cell lines with wt and functional P53 than in mutated P53 cell lines. However, apoptosis was also induced in JJN3 cells, which although they do not carry the P53 mutation, do have impaired activity of the p53 pathway.…”
Section: Discussionsupporting
confidence: 50%
“…34), and liver cancer (IGFBP5; ref. 35). Many cancer-related genesets and several oncogenic signatures were enriched in genes upregulated in transformed Smchd1-null MEFs and/or tumors, including E2F3 (29 genes, P < 0.05), E2F1/E2F (2 genesets, P < 0.05), and BRCA1/2 pathways (5 genesets, P < 0.01), which may explain the accelerated tumor growth in the absence of Smchd1.…”
Section: Smchd1 Deficiency Leads To Increased Clonogenicity Of Premalmentioning
confidence: 97%